Sense and content of the term “Flow of money” - Sokolova, N. S.; Sokolova, T. H. (Science and Transport Progress, 2011)
The matter and content of the cash flows of any organization have been analyzed, the fundamentals to the determination of the cash flows have been singled out, the concept of cash flow have been defined more precisely.